Money and mental wellbeing: a longitudinal study of medium-sized lottery wins - Jonathan Gardner; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2006)
One of the famous questions in social science is whether money makes people happy. We offer new evidence by using longitudinal data on a random sample of Britons who receive medium-sized lottery wins of between 1000 and 120,000 (that is, up to approximately U.S. 200,000). When compared to two control groups - one with no wins and the other with small wins - these individuals go on eventually to exhibit significantly better psychological health. Two years after a lottery win, the average measured improvement in mental wellbeing is 1.4 GHQ points.
Keywords: D1; I3; 330; Glücksspiel; Einkommen; Großbritannien